Improvement of the Functional Parameter in Patient with Chronic Obstructive Pulmonary Disease after Pulmonary Rehabilitation - Arifin SWA; Indra R; Siti Chandra Widjanantie; Nury Nusdwinuringtyas (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Functional parameter in Chronic Obstructive Pulmonary Disease (COPD) can be evaluated withPeak Cough Flow (PCF), as an effective tool to measure cough ability. Patients with COPD can not do cougheffectively, that leads to sputum retention and finally functional capacity. The aimed of the study to foundimprovement of cough ability (PCF) and COPD symptom.Methods:This was a retrospective cohort study. The researcher did the measurement for PCF, COPD assesmenttool (CATTM ) score and the sixt minute walking test (6MWT) on COPD patients, after rehabilitation programthree times a week, for four weeks. The program consisted of infrared diathermy, breathing exercise, chestmobility exercise, the active cycle breathing technique and static cycle or treadmill exercise program betweenJanuary-June 2018.Results: Subjects are ten COPD patients, the mean of age was 70 years old. The data of PCF, CATTM, anddistance of 6MWT before intervention were 246± 57.19 L/ minute, 13.1± 6.36, and 296.4± 79.30. Thereforethe PCF, CATTM, and distance in 6MWT after four weeks intervention were 269 ± 70.78 (p< 0.05), 15.2 ± 8.56(p> 0.05), and 339.3 ± 62.55 (p> 0.05).Conclusion: Rehabilitation program on COPD patient along four weeks improve the PCF, however did notimprove the CATTM score and the distance of 6MWT.Keywords: 6 Minute Walk Test (6MWT), Chronic Obstructive Pulmonary Disease (COPD), COPD Assesment Test(CAT) Score, Functional Parameter, Peak Cough Flow (PCF).